Two new species of Ommatius Wiedemann (Diptera: Asilidae) from Brazil - Vieira, Rodrigo; Castro, Ivan; Bravo, Freddy (Zootaxa, 2004)
Ommatius cinthiae sp. nov. and O. serrajiboiensis sp. nov. are described from an Atlantic Forest area in northeastern Brazil. These two species belong to the costatus species group, thus increasing the number of known species of this neotropical group to sixteen.